2009
DOI: 10.2139/ssrn.1332071
|View full text |Cite
|
Sign up to set email alerts
|

Goals Gone Wild: The Systematic Side Effects of Over-Prescribing Goal Setting

Abstract: Goal setting is one of the most replicated and influential paradigms in the management literature.Hundreds of studies conducted in numerous countries and contexts have consistently demonstrated that setting specific, challenging goals can powerfully drive behavior and boost performance. Advocates of goal setting have had a substantial impact on research, management education, and management practice. In this article, we argue that the beneficial effects of goal setting have been overstated and that systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 58 publications
0
42
0
2
Order By: Relevance
“…Although goal setting has been shown to have a positive influence on task performance (Locke & Latham, , , ), since the early days of goal setting research, the possibility of negative side effects has been acknowledged (Locke & Latham, ). More recently, Ordóñez, Schweitzer, Galinsky, and Bazerman () suggested that goal setting “may cause systematic problems in organizations due to narrowed focus, increased risk taking, unethical behavior, inhibited learning, decreased cooperation, and decreased intrinsic motivation” (p. 14). Instead of prescribing goal setting as an “all‐purpose remedy for employee motivation,” they argue that goal setting is like a strong prescription drug that can have adverse side effects, that it should be applied with caution, and that it should come with a warning label.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although goal setting has been shown to have a positive influence on task performance (Locke & Latham, , , ), since the early days of goal setting research, the possibility of negative side effects has been acknowledged (Locke & Latham, ). More recently, Ordóñez, Schweitzer, Galinsky, and Bazerman () suggested that goal setting “may cause systematic problems in organizations due to narrowed focus, increased risk taking, unethical behavior, inhibited learning, decreased cooperation, and decreased intrinsic motivation” (p. 14). Instead of prescribing goal setting as an “all‐purpose remedy for employee motivation,” they argue that goal setting is like a strong prescription drug that can have adverse side effects, that it should be applied with caution, and that it should come with a warning label.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of prescribing goal setting as an “all‐purpose remedy for employee motivation,” they argue that goal setting is like a strong prescription drug that can have adverse side effects, that it should be applied with caution, and that it should come with a warning label. In a response to Ordóñez et al (), Locke and Latham () suggested that the evidence against goal setting is largely anecdotal and that the standards for good scholarship demand that more empirical work be carried out before any claims regarding adverse effects can be made. The findings of this research draw attention to a negative side effect of goal setting in which moderately difficult goals lead individuals to continue a failing course of action.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is only indirect evidence from the work of Schweitzer, Ordonez and Douma (2004) and Lehman and Ramanujam (2009), who found that people with unmet goals were more likely to violate rules and to engage in unethical behavior. Additionally, there is anecdotal evidence such as the examples given by Ordonez, Schweitzer, Galinsky and Bazerman (2009). While further experiments are needed to investigate the influence of the interaction of different organizational factors, the results of this study clearly indicate that newly introduced safety rules (which always come with some effort) are vulnerable to violation if the management fails to frame them as a sure gain for company and workers.…”
Section: Discussionmentioning
confidence: 77%
“…Es existieren Vorbehalte gegen den konsequenten Einsatz von Controlling (auch wenn hier teilweise bereits die BSC eingesetzt wird) insbesondere bei Einrichtungen der öffentlichen Hand, von Wohlfahrtsverbänden oder kirchlichen Trägern. Schon beim Einsatz "einfacher" ControllingInstrumente, kann es zu Konflikten zwischen flexibler Dienstleistung am Menschen und klaren, messbaren Ziel-und Leistungsvorgaben und somit zu Widerständen bei den handelnden Personen kommen [21].…”
Section: Die Bsc Im Gesundheitswesenunclassified